The role of repeat kidney biopsy in patients with lupus nephritis (case report) - N. Yu. Nikishin; E. A. Aseeva; A. A. Mesnyankina; S. K. Soloviev; E. S. Stolyarevich; V. A. Zelenov; A. M. Lila (Современная ревматология)
Lupus nephritis (LN) occurs in 35–60% of patients with systemic lupus erythematosus (SLE), often in the early stages of the disease. LN is one of the most severe manifestations of SLE and, if not treated promptly and effectively, can lead to rapid and severe loss of kidney function. Despite modern pharmacotherapy, 5–20% of patients develop end-stage renal failure within 10 years of diagnosis of LN. The main principle of LN therapy is to prevent deterioration of renal function, but a consensus on outcome assessment criteria and clinically relevant short- and long-term goals for LN therapy has not yet been reached. There is increasing evidence of the importance of repeat kidney biopsies to assess the outcomes of the initial phase of therapy and to determine the long-term prognosis of renal failure. It is believed that the information obtained from repeat biopsies can help to make optimal treatment decisions and thus increase the likelihood of achieving a complete renal response in the short term and a more favorable renal prognosis in the long term.We describe a clinical case of a young patient with highly active SLE and morphologically confirmed class IV-S LN. Repeat biopsy and clinical and laboratory examination, had confirmed a clinical and laboratory remission of the disease on the background of the therapy. This made it possible to reduce the dose of methylpednisolone and cytostatic drugs (mycophenolate mofetil) and to discontinue therapy with biologic diseasemodifying antirheumatic drug (rituximab).